2015
DOI: 10.1159/000374041
|View full text |Cite
|
Sign up to set email alerts
|

Potential Antifibrotic and Angiostatic Impact of Idebenone, Carnosine and Vitamin E in Nano-Sized Titanium Dioxide-Induced Liver Injury

Abstract: Background/Aim: The present study investigated the in vitro and in vivo effects of individual and combined doses of idebenone, carnosine and vitamin E on ameliorating some of the biochemical indices of nano-sized titanium dioxide (n-TiO2) in mice liver. Methods: The in vitro cytotoxic effect of nano-sized anatase TiO2 (21 nm) on hepatic cell lines (HepG 2) was investigated. Additionally, n-TiO2 was orally administered (150 mg/kg/day) for 2 weeks, followed by a daily intragastri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…The activities of antioxidant enzymes, including catalase, SOD and GPx, were increased by vitamin E in the liver of ethanol-administered rats [140]. Furthermore, it was shown that vitamin E decreased liver fibrosis in male Wistar albino mice-treated with nano-sized titanium dioxide (n-TiO 2 ), a metallic nanoparticle generating inflammatory responses, apoptosis and necrosis via the stimulation of ROS production [143].…”
Section: Food Components For the Prevention Of Liver Fibrosismentioning
confidence: 99%
“…The activities of antioxidant enzymes, including catalase, SOD and GPx, were increased by vitamin E in the liver of ethanol-administered rats [140]. Furthermore, it was shown that vitamin E decreased liver fibrosis in male Wistar albino mice-treated with nano-sized titanium dioxide (n-TiO 2 ), a metallic nanoparticle generating inflammatory responses, apoptosis and necrosis via the stimulation of ROS production [143].…”
Section: Food Components For the Prevention Of Liver Fibrosismentioning
confidence: 99%
“…Different superscript letters in the same row indicate significant differences at p < 0.05. fibrosis factors that arise from the Kupffer cells and endothelial cells. These factors are responsible for increasing collagen synthesis 1, 3, and 4; therefore, increased expression of such factors is common in cases of the fibrosis and the necrosis accompanied by inflammation, it plays an important role in the fibrogenesis (Chobert et al 2012;Abdelazim et al 2015). Our results regarding the effects of Ag-BSEPS administration revealed significantly reduced concentrations of TNF-α, IL-6, IL-1β, and TGF-β, compared to the TAA group.…”
Section: Discussionmentioning
confidence: 51%
“… 31 The obtained results showed that S.nit toxicity produced a marked upregulation in the Flt-1 level, which was downregulated by L-argin, carno, or their combination. Abdelazim et al 32 reported that carno downregulated the overexpression of flt-1, Smad-2, IL-6, and TNF-α and the angiogenic factor VEGF in response to n-TiO 2 intoxication.…”
Section: Discussionmentioning
confidence: 99%